Anti‐phospholipid antibodies and reproductive failures. (15th May 2020) - Beltagy, Asmaa; Trespidi, Laura; Gerosa, Maria; Ossola, Manuela Wally; Meroni, Pier Luigi; Chighizola, Cecilia B.
Abstract: Anti‐phospholipid syndrome (APS) recapitulates the link between autoimmunity and pregnancy failure: Acquired anti‐phospholipid antibodies (aPL) play a pathogenic role in pregnancy complications. The diagnosis of obstetric APS can easily be pursued when women present with laboratory and clinical features fulfilling the international classification criteria. Standard therapeutic approach to obstetric APS consists in the association of anti‐platelet agents and anticoagulants. Most patients achieve a live birth thanks to conventional treatment; however, approximately 20% fail to respond and are managed with additional therapeutic tools added on the top of conventional treatment. Surely, a refinement of risk stratification tools would allow early identification of high‐risk pregnancies that warrant tailored treatment. In real life, obstetricians and rheumatologists face complex diagnostic scenarios including women with pregnancy morbidities other than those mentioned in classification criteria such as one or two early losses and premature birth after 34 weeks due to preeclampsia or placental insufficiency, women with low‐titer aPL not fulfilling criteria laboratory requirements, women with positive non‐criteria aPL, asymptomatic aPL carriers, and infertile women found to be aPL‐positive. This review focuses on some of the several unanswered questions related to diagnostic, prognostic, and therapeutic aspects in obstetric APS.